No way out but one [videorecording (DVD)] - Collins, Holly (Holly Ann); Waller, Garland; Waller, Garland; Waller, Garland; Nolan, Barry, 1947-; Nolan, Barry, 1947-; Nolan, Barry, 1947-; Nolan, Barry, 1947- (Passion River Films, 2013)
Holly Collins came to the family court of Minnesota with the intention of bringing charges of domestic violence against her ex-husband. The courts granted full custody of her children to her and her children's abuser. In 1994, Holly Collins became an international fugitive when she ignored the court's ruling, grabbed her three children, and went on the run from her abusive ex-husband.